1984
DOI: 10.1111/j.1469-8137.1984.tb03609.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF PHOSPHORUS ON THE FORMATION OF HYPHAE IN SOIL BY THEVESICULAR‐ARBUSCULAR MYCORRHIZAL FUNGUS, GLOMUS FASCICULATUM

Abstract: Summary Hyphae formed in soil by the vesicular‐arbuscular (VA) mycorrhizal fungus, Glomusfasciculatum (Thaxter sensu Gerd.) Gerd. and Trappe were extracted using the membrane filter techniqe and their length was estimated by the grid intersection method. The effect of phosphorus on the formation of this external mycelium was assessed after sampling procedures had been investigated. Phosphorus supply was varied from amounts severely deficient to those adequate for the growth of subterranean clover. After 6 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
131
1
3

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(156 citation statements)
references
References 30 publications
21
131
1
3
Order By: Relevance
“…The total EM increased with time and reached about 19 m g -1 in the substrate with +AMF plants at 90 DAT, in all P levels. These data are in agreement with previous works (Abbott et al, 1984;Schubert et al, 1987;Sylvia, 1988;Li et al, 1991), in which the total EM ranged from less than 1 to about 26 m g -1 .…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The total EM increased with time and reached about 19 m g -1 in the substrate with +AMF plants at 90 DAT, in all P levels. These data are in agreement with previous works (Abbott et al, 1984;Schubert et al, 1987;Sylvia, 1988;Li et al, 1991), in which the total EM ranged from less than 1 to about 26 m g -1 .…”
Section: Resultssupporting
confidence: 83%
“…Total EM and active EM always had higher figures in the substrate with +AMF plants, at all P levels, along the experiment. Although some authors (Abbott et al, 1984;Sylvia, 1988;Li et al, 1991) suggested the subtraction of the mycelium estimated in -AMF treatments from their respective +AMF counterparts, both data were presented, because it is quite difficult to distinguish mycorrhizal mycelium from that from other filamentous fungi (Sylvia, 1988;Kabir et al, 1996;. In addition, interactions between AMF and saprophytic fungi are unknown, whether stimulating or inhibiting each other.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total and mycorrhizal root length was determined for RC and RHC by a line-intersect method (Tennant, 1975) after staining root subsamples in trypan blue (Kormanik & McGraw, 1982). Length of mycorrhizal hyphae was measured using a membrane filter-grid intersect method modified after Abbott, Robson & De Boer (1984). Modifications included the use of 2 ml aliquots and 20 mm diameter filter area.…”
Section: Harvest and Analysesmentioning
confidence: 99%